ANALISIS YURIDIS PEMBERIAN INSENTIF PAJAK TERHADAP WAJIB PAJAK YANG TERKENA DAMPAK PANDEMI VIRUS CORONA DI KOTA MEDAN - Lusia Sirait; Michael Luahambowo; Willy Tanjaya (Jurnal Ilmiah Advokasi, 2021)
In the event of a worldwide pandemic,the government will of course continue to draft laws to address the problems caused by the corona virus in Indonesia's tax system.Some of its policies,particularlyi nthe area of taxation,are designed to create incentives.Incentives to collect taxes and levies are additional moneyÂ  offered in exchange for a certain level of performance in enforcing taxes and levies.Government incentives are intended to boost the country's economy.This study uses a descriptive research design and empirical normative research techniques.This research includes some original data,such as source interviews,as well as secondary data,such asprimary,secondary,and tertiary legal publications.The government through the Directorate General of Taxes has developed a reporting system for the use of tax incentives for taxpayers that facilitates reporting.However,there are still many obstacles in its implementation at KPP Pratama Medan,and many taxpayers are not aware of the tax incentives available during theCOVID-19 pandemic.Keywords: Economic Stimulus,Tax Incentives,Corona Virus Pandemi